Accounting for Derivatives - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2005)
The chapter explains the implications of International Accounting Standard 39 on financial reporting with respect to how the standard changes the landscape of historical cost reporting through requiring financial instruments to be measured at fair value. The chapter also analyzes the impact of hedge accounting rules on corporate reporting.